The Role Of Forensic Accounting Curriculum In Forensic Audit - Perwita Sari, Rida; Agussalim, Agussalim; Mahsun, Muhamad; Puspita Sari, Rika (International Journal of Educational Research & Social Sciences, 2022)
The purpose of the study is to identify the gap between the practice requirements and the outputs of the audit education and training center and to identify the contribution of the forensic accounting curriculum in filling the gap. This study uses a quantitative approach. The sample is 124 respondents with professional backgrounds as auditors and accountants educators in Indonesia. The data collection method implemented in this research is the survey method through the distribution of questionnaires and direct interview techniques with the non-participatory observation which aims to find out more details about the case being studied without actively involving the object of study. Furthermore, this study explores the best possible strategies in shaping learning outcomes that are competent and ready to practice as auditors based on various previous studies and contributes to auditing education and training centers and universities by providing material for consideration in the preparation of strategic plans and learning programs. This study can also contribute to prospective auditors who are considering alternative audit training curricula by providing various competency recommendations for the needs of current auditing practices.